Role of the circulation on the anthropogenic CO2 inventory in the North-East Atlantic: A climatological analysis - Carracedo, Lidia; Perez, Ff; Gilcoto, M.; Velo, A.; Padin, A.; Roson, G. (Progress in Oceanography, 2018)
Climatology-based storage rate of anthropogenic CO2 (C-ant, referred to year 2000) in the North-East Atlantic (53 +/- 9 kmol s(-1), 0.020 +/- 0.003 Pg-C yr(-1)) is described on annual mean terms. C-ant advection (32 +/- 14 kmol s(-1)) occurs mostly in the upper 1800 m and contributes to 60% of the C-ant storage rate. The Azores and Portugal Currents act as 'C-ant streams' importing 389 +/- 90 kmol s(-1), most of which recirculates southwards with the Canary Current (-214 +/- 34 kmol s(-1)). The Azores Counter Current (-79 +/- 36 kmol s(-1)) and the northward-flowing Mediterranean Water advective branch (-31 +/- 12 kmol s(-1)) comprise secondary C-ant export routes. By means of C-ant transport decomposition, we find horizontal circulation to represent 11% of the C-ant storage rate, while overturning circulation is the main driver (48% of the C-ant storage rate). Within the domain of this study, overturning circulation is a key mechanism by which C-ant in the upper layer (0-500 dbar) is drawdown (74 +/- 14 kmol s(-1)) to intermediate levels (500-2000 dbar), and entrained (37 +/- 7 kmol s(-1)) into the Mediterranean Outflow Water to form Mediterranean Water. This newly formed water mass partly exports C-ant to the North Atlantic at a rate of -39 +/- 9 kmol s(-1) and partly contributes to the C-ant storage in the North-East Atlantic (with up to 0.015 +/- 0.006 Pg-C yr(-1)). Closing the C-ant budget, 40% of the C-ant storage in the North-East Atlantic is attributable to anthropogenic CO2 uptake from the atmosphere (21 +/- 10 kmol s(-1)).